Assessment of Integrated Safety-security Barriers Performance to Support the Management of Industrial Installations - Valeria Casson Moreno; Giulia Marroni; Michela Guarguaglini; Sanneke Kuipers; Gabriele Landucci (Chemical Engineering Transactions)
The assessment of accident scenarios linked to intentional attacks on chemical and process facilities has gained significant attention due to escalating conflicts in critical contexts. This work presents a methodology for the quantitative integration of safety and security aspects within the Event Tree Analysis (ETA), a widely used tool in Quantitative Risk Assessment (QRA). Firstly, the conceptual framework is established: safety and security barriers are identified, and classified based on the functions and working principles. Then, the performance of the barriers is studied in terms of availability and efficiency. This support the incorporation of the barriers into the ETA using tailored decisional gates and quantifying the probability of escalation due to external attacks. The application of the methodology to a demonstration case study next shows its potential: safety barriers effectively mitigate the escalation probability of intentional attacks, reducing plant vulnerability and providing a clearer understanding of facility criticalities. The proposed methodology can seamlessly integrate into existing QRA studies, offering a unified framework to enhance risk-based decision-making and resource allocation.